KESENJANGAN GENDER DAN KESETARAAN KETENAGAKERJAAN: SEBUAH TINJAUAN - Suryono Efendi (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2018)
The purpose of this article is to discuss Employment Equity and many sub-issues including male domination in organizations, target groups, government policies, and quota systems. This study attempts to address the topic of whether equality in the mirror is only "sweet words without meaning" that glosses over women's failings in the name of the organization's dedication to women's advancement. Thus, workplace equality is a concern for growth that is entirely balanced on the basis of merit and ability, as well as aggressively supporting good women and minorities without regard for bias or prejudice. Perfect workplace equity contributes to the organization's attractiveness as a place to work and strengthens the organization's image of social responsibility.